Morphology, Carbohydrate Distribution, Gene Expression, and Enzymatic Activities Related to Cell Wall Hydrolysis in Four Barley Varieties during Simulated Malting - Betts, Natalie S.; Wilkinson, Laura G.; Khor, Shi F.; Shirley, Neil J.; Lok, Finn; Skadhauge, Birgitte; Burton, Rachel A.; Fincher, Geoffrey B.; Collins, Helen M. (Frontiers in Plant Science, 2017)
Many biological processes, such as cell wall hydrolysis and the mobilisation of nutrient reserves from the starchy endosperm, require stringent regulation to successfully malt barley (Hordeum vulgare) grain in an industrial context. Much of the accumulated knowledge defining these events has been collected from individual, unrelated experiments, and data have often been extrapolated from Petri dish germination, rather than malting, experiments. Here, we present comprehensive morphological, biochemical and transcript data from a simulated malt batch of the three elite malting cultivars Admiral, Navigator and Flagship and the feed cultivar Keel. Activities of lytic enzymes implicated in cell wall and starch depolymerisation in germinated grain have been measured, and transcript data for published cell wall hydrolytic genes have been provided. It was notable that Flagship and Keel exhibited generally similar patterns of enzyme and transcript expression, but exhibited a few key differences that may partially explain Flagship’s superior malting qualities. Admiral and Navigator also showed matching expression patterns for these genes and enzymes, but the patterns differed from those of Flagship and Keel, despite Admiral and Navigator having Keel as a common ancestor. Overall (1,3;1,4) β glucanase activity differed between cultivars, with lower enzyme levels and concomitantly higher amounts of (1,3;1,4) β glucan in the feed variety, Keel, at the end of malting. Transcript levels of the gene encoding (1,3;1,4) β glucanase isoenzyme EI were almost three times higher than those encoding isoenzyme EII, suggesting a previously unrecognised importance for isoenzyme EI during malting. Careful morphological examination showed that scutellum epithelial cells in mature dry grain are elongated but expand no further as malting progresses, in contrast to equivalent cells in other cereals, perhaps demonstrating a morphological change in this critical organ over generations of breeding selection. Fluorescent immuno-histochemical labelling revealed the presence of pectin in the nucellus and, for the first time, significant amounts of callose throughout the starchy endosperm of mature grain.